Sintesis Biodiesel dari Minyak Jelantah menggunakan Katalis Heterogen Berbasis Kalsium Oksida dari Limbah Cangkang Kerang Bulu (Anadara antiquata) - Rahmat, Anni; Kurniati, Yuni; Rahmah Hidayah, Laila; Nafisah, Salwa (Universitas Trunojoyo Madura, 2025)
The depletion of non-renewable fossil energy reserves is the main reason for this research to develop renewable energy as a substitute for diesel fuel. One of the alternatives studied is the production of biodiesel from used cooking oil. This study aims to produce environmentally friendly biodiesel, reduce dependence on fossil energy, and utilize used cooking oil waste to increase its value for society. This research employs esterification and transesterification methods. The variations in the catalyst used are 2 grams, 4 grams, and 6 grams. Meanwhile, the oil-to-methanol ratio is applied at 1:1.5, 1:3, and 1:6. The results of this study indicate that the free fatty acid content of used cooking oil must be at least 1% to proceed with the transesterification process. Calcium oxide (CaO) catalyst derived from Anadara antiquata shell waste, used as a heterogeneous base catalyst, contains 96.51% CaO. The best biodiesel yield was obtained at a molar ratio of 1:1.5 with 6 grams of catalyst, a molar ratio of 1:6 with 2 grams of catalyst, and a molar ratio of 1:6 with 4 grams of catalyst. All three samples met the biodiesel test standards according to the National Standard (SNI. This study tested the flame on biodiesel. During combustion, the flame color is produced by rapid oxidation. The color indicates the amount of energy produced. Blue flames emit more heat than red flames. Red flames are present below 1000°C. Blue flames are present at temperatures below 2000°C. The combustion of samples containing biodiesel produced a blue flame.